Assessment of the Safety and Efficacy of an Oral Probiotic-Based Vaccine Against Aspergillus Infection in Captive-Bred Humboldt Penguins (Spheniscus humboldti) - Thorel, Milan; Mateos-Hernandez, Lourdes; Mulot, Baptiste; Azzouni, Mouna Naila; Hodžić, Adnan; Gaillot, Hugues; Ruel, Yannick; Desoubeaux, Guillaume; Delaye, Jean-Baptiste; Obregon, Dasiel; Wu-Chuang, Alejandra; de la Fuente, José; et al. (Frontiers in Immunology, 2022)
Aspergillosis is a fungal infection caused mainly by Aspergillus fumigatus that commonly often results in respiratory disease in birds. Aspergillosis is a major cause of morbidity and mortality in managed penguin species. Currently, there is no registered vaccine to prevent aspergillosis. Recent research demonstrated that oral administration of gram-negative bacteria expressing high levels of galactose-α-1,3-galactose (α-Gal) modulates anti-α-Gal immunity and protectes turkeys from clinical aspergillosis caused by experimental A. fumigatus infection. The role of anti-α-Gal immunity in penguins has not been studied. Here, we tested the distribution of α-1,3-galactosyltransferase (α1,3GT) genes in the fecal microbiome of Humboldt penguins (Spheniscus humboldti). The occurrence of natural anti-α-Gal antibodies (Abs) in sera and eggs of healthy Humboldt penguins was also assessed. A trial was then conducted to test whether oral administration of Escherichia coli Nissle, expressing high α-Gal levels, modulated anti-α-Gal immunity in a colony of managed Humboldt penguins. Animals in the vaccination and placebo groups were evaluated before the trial and followed for one year for aspergillosis detection using a diagnostic panel including computed tomography scans, capillary zone electrophoresis, 3-hydroxybutyrate levels, and anti-A. fumigatus Abs. Anti-α-Gal Abs were detected in sera (IgM and IgY) and eggs (IgY) of healthy penguins. Microbiota analysis and functional predictions revealed the presence of α1,3GT genes in the microbiota of Humboldt penguins and other penguin species. A strong decrease of anti-α-Gal IgM levels was observed in all animals in the placebo group three months after vaccination protocol. This decrease was not observed in E. coli Nissle-treated penguins. After the vaccination protocol, we found a positive correlation between anti-E. coli IgY and anti-α-Gal IgY in the E. coli Nissle group, suggesting a correlation between the presence of the bacteria and these Abs. During the study period, three penguins exhibited respiratory signs consistent with aspergillosis. Two were from the placebo group whose symptoms resolved with specific treatments, while a single vaccinated individual developed fatal respiratory aspergillosis eight months after the trial. We conclude that E. coli Nissle represents a safe potential probiotic with protective effect against aspergillosis in Humboldt penguins that deserves to be further explored for therapeutic use.